Development and validation of the Palliative Care Knowledge Scale (PaCKS). Issue 5 (27th December 2016) - Kozlov, Elissa; Carpenter, Brian D.; Rodebaugh, Thomas L.
ABSTRACT: Objective: The purpose of this study was to develop a reliable and valid scale that broadly measures knowledge about palliative care among non-healthcare professionals. Method: An initial item pool of 38 true/false questions was developed based on extensive qualitative and quantitative pilot research. The preliminary items were tested with a community sample of 614 adults aged 18–89 years as well as 30 palliative care professionals. The factor structure, reliability, stability, internal consistency, and validity of the 13-item Palliative Care Knowledge Scale (PaCKS) were assessed. Results: The results of our study indicate that the PaCKS meets or exceeds the standards for psychometric scale development. Significance of results: Prior to this study, there were no psychometrically evaluated scales with which to assess knowledge of palliative care. Our study developed the PaCKS, which is valid for assessing knowledge about palliative services in the general population. With the successful development of this instrument, new research exploring how knowledge about palliative care influences access and utilization of the service is possible. Prior research in palliative care access and utilization has not assessed knowledge of palliative care, though many studies have suggested that knowledge deficits contribute to underutilization of these services. Creating a scale that measures knowledge about palliative care is a critical first step toward understanding and combating potential barriers to access and utilization of this life-improving service.